Exploring the sustainable food security approach in relation to agricultural and multi-sectoral interventions: A review of cross-disciplinary perspectives. Issue 108 (January 2020) - Farrukh, Muhammad Umer; Bashir, Muhammad Khalid; Rola-Rubzen, Fay
Abstract: Agricultural interventions alone will fail to achieve sustainable food security outcomes. Hence, it is important to investigate multi-sectoral linkages, especially the role of rural women and trade. Many have studied available evidence of ways in which agricultural interventions can be leveraged to achieve food security; however, none of them have employed a cross-disciplinary pathways approach that ensure internal and external validity. This study fills this gap by exploring sustainable food security approaches employing a DFID framework. The review analysis shows that agricultural interventions and multi-sectoral linkages have the potential to enhance food security. The study then draws on the implications for Pakistan, whose contemporary food security challenges demand a well-designed integrated approach to bridge the gap between scale and disciplines of analysis. In the end, this study advocates a mixed-methods approach for strengthening policy recommendations for Pakistan. The integrated dataset can also be useful in providing empirical insights into the food security outcomes at the national, household and individual level.